Misdiagnosis of Susac syndrome as demyelinating disease and primary angiitis of the central nervous system: A case report - Wu, Gang; Jiang, Wei; Li, Zunbo; Huang, Dehui; Wu, Lei (Frontiers in Neurology, 2022)
Susac syndrome (SuS) is a rare neuroinflammatory disease that manifests with a triad of hearing loss, branch retinal artery occlusions, and encephalopathy. Patients with SuS are frequently misdiagnosed because the clinical triad is incompletely present at disease onset. Herein, we present a case of a 29-year-old man manifesting sleepiness, epilepsy, urinary dysfunction, and hemiparesis at the initial stage. Magnetic resonance imaging (MRI) revealed multiple abnormal signals located in the lateral paraventricular, corpus callosal, and pons. In addition, the patient had sustained elevation of CSF pressure and protein. ADEM was considered according to the clinical and radiographic findings. However, symptoms were not significantly improved after methylprednisolone therapy. He showed vision decline in the third month after the disease onset. It was considered from intracranial hypertension or optic neuritis, and therefore retinal arteriolar impairment was ignored. As the disease progresses, cognitive decline was presented. Brain MRI exhibits multiple significant hyperintensities on the DWI sequence with speck-like gadolinium enhancement. Thus, PACNS was diagnosed. The SuS was not made until the presence of hearing decline in the four months after the disease onset. The case will be helpful for clinicians to better recognize the atypical initial manifestation of SuS.